UTILIZING LINGUISTICS LANDSCAPE IN PROJECT-BASED LEARNING IN TEACHING WRITING IN JUNIOR HIGH SCHOOL - Devi, Madhu Sri; Padmadewi, Ni Nyoman; Artini, Luh Putu (Universitas Suryakancana, 2024)
This study investigates the effectiveness of the Linguistic Landscape (LL) Technique through Project-Based Learning (PjBL) on seventh-grade students' writing skills at SMP PGRI 2 Denpasar. Industry 4.0's influence on education underscores the need for innovative strategies aligning with the 6C framework. Communication, a vital skill, is often challenging for students, prompting a focus on writing skills as a remedy. Project-Based Learning, particularly when incorporating Linguistic Landscape, emerges as a promising approach. This study employs a mixed-methods approach that utilizes a pre-experimental design involving tests, questionnaires, and interviews for data collection. As a result, the study demonstrates the positive impact of integrating Project-Based Learning (PjBL) and Linguistic Landscape (LL) on enhancing the writing skills of seventh-grade students at SMP PGRI 2 Denpasar. The findings emphasize the importance of innovative pedagogical approaches in preparing students for the demands of the evolving educational landscape